2008
DOI: 10.1007/s12088-008-0024-3
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in aquaculture: importance and future perspectives

Abstract: Aquaculture is one of the fastest developing growth sectors in the world and Asia presently contributes about 90% to the global production. However, disease outbreaks are constraint to aquaculture production thereby affects both economic development of the country and socio-economic status of the local people in many countries of Asia-Pacifi c region. Disease control in aquaculture industry has been achieved by following different methods using traditional ways, synthetic chemicals and antibiotics. However, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
89
0
12

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(102 citation statements)
references
References 57 publications
1
89
0
12
Order By: Relevance
“…Probiotics are known as live microbial additives which exert their useful impacts (improvement of digestion and absorption of nutrients utilization, nutritional value, growth and resistance against pathogens) on host by modifying of microbial community of gut (Ringø and Gatesoupe 1998;Vershuere et al 2000;Irianto and Austin 2002a;Sahu et al 2008). Also, prebiotics are substrates that promote selectively the growth one or number of bacterial community in gut and hence help to loading of health-promoting microflora in gut, thus improving host welfare (Yazawa et al 1978;Gibson and Roberfroid title of synbiotics or synbiotic supplement can be more efficient than applying them alone (Chou et al 1991;Hagi and Hoshino 2009;Lauzon et al 2010;Montajami et al 2012;Nekoubin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are known as live microbial additives which exert their useful impacts (improvement of digestion and absorption of nutrients utilization, nutritional value, growth and resistance against pathogens) on host by modifying of microbial community of gut (Ringø and Gatesoupe 1998;Vershuere et al 2000;Irianto and Austin 2002a;Sahu et al 2008). Also, prebiotics are substrates that promote selectively the growth one or number of bacterial community in gut and hence help to loading of health-promoting microflora in gut, thus improving host welfare (Yazawa et al 1978;Gibson and Roberfroid title of synbiotics or synbiotic supplement can be more efficient than applying them alone (Chou et al 1991;Hagi and Hoshino 2009;Lauzon et al 2010;Montajami et al 2012;Nekoubin et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fish S. baicalensis is known to boost the immune system [20]. Triherbal solvent extracts from Azadirachta indica, Ocimum sactum, and Curcuma longa have been reported that enhanced innate immunity in goldfish against Aeromonas hydrophila [21,22]. In rainbow trout dietary administration of probiotics also enhanced the innate immunity against Yersinia ruckeri [22].…”
Section: Introductionmentioning
confidence: 99%
“…This level of production had a value of US$70.3 billion. In this production, 41.3 million tones, or 69.6 %, was produced in China and 21.9 % in the rest of Asia and the Pacific region [13].…”
Section: Introductionmentioning
confidence: 99%